ANALISIS STRUKTUR DAN NILAI PENDIDIKAN NOVEL DIRAWU KÉLONG KARYA AHMAD BAKRI SEBAGAI BAHAN PEMBELAJARAN - Siti Aminah; Opah Ropiah (Prodi Pendidikan Bahasa dan Sastra Daerah, 2022)
This study aims to: 1) analyze the structure of the novel Dirawu Kélong by Ahmad Bakri; 2) analyze the educational value of Ahmad Bakri's Dirawu Kélong novel; 3) as well as for learning materials for reading novels in class IX SMP. This research is qualitative research with a descriptive analysis method. The technique of collecting data using the literature study technique and the data source is the novel Dirawu Kélong by Ahmad Bakri. The results of this study are: 1) this novel is themed about the daily life of Udin, the lines used are mixed lines, and the 18 characters involved. The mandate contained in it is to advise about life so that you can think long, respect all God's creatures, and be obedient to your parents; 2) Analysis of educational values ​​in the Dirawu Kélong novel includes character education values, namely religious, honest, tolerance, discipline, hard work, creative, independent, democratic, curiosity, national spirit, love peace, love to read, care for the environment, responsibility; 3) the novel Dirawu Kélong deserves to be used as a learning material for reading novels in grade IX SMP because it covers aspects of language, psychology, and cultural background..